Capital Punishment and the Legacies of Slavery and Lynching in the United States. (March 2021) - Rigby, David; Seguin, Charles
Capital punishment in the United States is racialized: those convicted of the murder of Whites are much more likely to receive the death penalty than those convicted for the murder of Blacks. Capital punishment is more commonly practiced in places where lynching of Blacks occurred more frequently and in states in which slavery was legal as of 1860. Accordingly, scholars have debated whether capital punishment reflects a legacy of lynching or a legacy of slavery. Our analysis shows that lynching on its own is a significant predictor of contemporary executions, but that once slavery is accounted for, slavery predicts executions, while lynching does not. We argue that slavery's state-level institutional legacy is central to contemporary capital punishment.